Subseafloor Biosphere Linked to Hydrothermal Systems 2014
DOI: 10.1007/978-4-431-54865-2_1
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of TAIGA Concept

Abstract: After the discovery of seafloor hydrothermal venting, it became evident that the subseafloor fluid advection system plays an extremely important role in the Earth's element cycle. We designate these fluid advections as sub-seafloor TAIGAs (which stand for Trans-crustal Advection and In-situ biogeochemical processes of Global sub-seafloor Aquifers. In Japanese, "taiga" refers to "a great river"). This concept emphasizes dynamic signature of subseafloor hydrosphere, especially for a hydrothermal fluid circulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Moreover, pair distribution function analyses showed that the Fh SRO particles were coated with poorly ordered Si. The Fh SRO in the iron mats of Lo 'ihi Seamount was not transformed to other Fe mineral phases during freezing, drying, and aging in seawater for up to 1 year, not even by heat treatment under oxidative conditions (98). Picard et al (99) demonstrated that the twisted stalk morphology was preserved at high temperature and pressure (250°C, 140 MPa).…”
mentioning
confidence: 99%
“…Moreover, pair distribution function analyses showed that the Fh SRO particles were coated with poorly ordered Si. The Fh SRO in the iron mats of Lo 'ihi Seamount was not transformed to other Fe mineral phases during freezing, drying, and aging in seawater for up to 1 year, not even by heat treatment under oxidative conditions (98). Picard et al (99) demonstrated that the twisted stalk morphology was preserved at high temperature and pressure (250°C, 140 MPa).…”
mentioning
confidence: 99%